Analysis of Construction Material Waste in a Four-Storey Office Shop Building Project - Asmi, Ade; Teguh Very Munandar,; Aurino Djamaris, (International Journal of Sustainable Construction Engineering and Technology, 2024)
The construction industry has experienced rapid growth in recent years, as evidenced by the development of roads, bridges, residential buildings, multi-storey structures such as apartments, offices, shopping centres, and other infrastructure projects. Material costs play a crucial role in determining the success of construction projects. This study adopts a quantitative research approach, using primary data collected through questionnaires distributed to respondents on-site. The responses were analysed using SPSS to identify the factors contributing to material waste during construction. Secondary data, including project cost estimates (Budget Estimate Plan), daily reports, and material purchase records, were also analysed. The study identifies three key factors contributing to material waste: inaccurate on-site measurements, leading to the overestimation of material volumes; complex design changes; and errors in the design during the construction phase. To minimise material waste, the study applies the waste hierarchy concept. The primary types of material waste identified were concrete, bricks, and reinforcing steel. Preventive measures suggested include improving the accuracy of material estimates and orders, tracking materials that can be reused or recycled, and repurposing leftover materials for other functions.